Exercise plus caloric restriction lowers soluble RAGE in adults with chronic kidney disease. (11th February 2020) - Malin, Steven K.; Navaneethan, Sankar D.; Fealy, Ciaran E.; Scelsi, Amanda; Huang, Hazel; Rocco, Michael; Kirwan, John P.
Summary: Introduction: The incidence of chronic kidney disease (CKD) has increased in recent years. CKD is associated with obesity, type 2 diabetes, and cardiovascular disease, although the mechanism remains unclear. Elevated soluble form of the receptor for advanced glycation end products ( RAGE) is related to proinflammatory signaling pathways that may promote diabetic nephropathy and vascular dysfunction. Because lifestyle modification reduces systematic inflammation in adults with obesity and hyperglycaemia, the hypothesis that exercise plus caloric restriction would lower soluble RAGE in adults with CKD was tested in this study. Methods: Eight adults (n = 6 females; age: 56.3 ± 2.8 y; BMI: 43.7 ± 2.2 kg/m 2 ; 2‐h OGTT glucose: 215 ± 9.8 mg/dL; eGFR: 49.6 ± 3.3 mL/min/1.73 m 2 ) were enrolled in a 12‐week pilot lifestyle intervention (supervised aerobic exercise [5 d/wk, up to 60 min/d at approximately 65%‐85% HRmax ] plus low‐fat dietary counseling). Body composition (DXA), aerobic fitness (VO2 max), insulin sensitivity (120 min 75 g OGTT; Matsuda Index), plasma levels of soluble RAGE and fetuin‐A were measured before and after the intervention. Results: Exercise reduced body weight, fasting glucose, and fetuin‐A as well as increased VO2 max, glucose tolerance, and insulin sensitivity (all P < .05). Lifestyle intervention decreased plasma soluble RAGE (pre: 1018.1 ± 163 vs post: 810.6 ± 119.6 ng/mL; P = .02), and the decrease was associated with a lower 2‐hour blood glucose ( r = 0.76, P = .03) and with increased insulin sensitivity ( r = −0.90, P < .01). Conclusions: Exercise and caloric restriction are effective at lowering soluble RAGE in relation to glucose regulation in patients with CKD.